Hubungan Lama Kontak dengan Kejadian Dermatitis Kontak Akibat Kerja pada Karyawan Salon di Kota Denpasar - Komang Trisna Sumadewi; Made Sudarjana; I Gusti Ngurah Bagus Jaya Wisesa (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Occupational contact dermatitis is a skin disease that arises due to work, which is generally caused by a history of contact with specific allergens and irritants at work or profession. The duration of contact is one of the factors influencing the incidence of occupational contact dermatitis. The longer contact duration with the chemical, the irritation or inflammation of the skin more likely will occur that can result a skin irritation. This study aims to determine the relationship between duration of contact and the incidence of occupational contact dermatitis of salon employees in Denpasar City. This study used an analytical study design with a cross-sectional approach. Cluster sampling used for sampling technique. The sample of this study is the salon employees in Denpasar City with a total of 38 people. Mathias criteria and NOSQ-2002 were used as research instruments. The data analysis technique used univariate and bivariate analysis using the Chi-Square test. The results showed that the majority of salon employees were aged 26-35 years (36.8%), female sex (86.6%), and have a contact duration < 5 hours (52.6%). The results of the bivariate analysis showed that there was a correlation between duration of contact and the incidence of occupational contact dermatitis in salon employees in Denpasar City (p = 0.001). This study can be concluded that there is a correlation between duration of contact and the incidence of occupational contact dermatitis of salon employees in Denpasar City.